Sliding doors: how their opening affects particulate matter levels?. (30th September 2020) - Della Camera, A; Spataro, G; Cevenini, G; Nante, N; De Marco, F M; Messina, G
Abstract: Background: The operating theatres (OTs) have adequate conditions to perform safe operations and to prevent surgical site infections. Opening doors can compromise these situations. Measurement of particulate contamination is a key point to check the effectiveness of preventive measures in the OTs. We analysed how openings impact in different type of OTs. Methods: Between January/February 2020 a transversal study was conducted in 5 different types of OTs in a university hospital. Two had laminar flows, with 55 and 60 air changes/h; three had turbulent flows: OT-A (18 air changes/h, with 4 inlets from the ceiling), OT-B (23 air changes/h and air flow from the ceiling plenum), OT-C (16 air changes/h, air flow directed from one wall to the opposite wall and the main door laterally to the flow). Particulate matter (PM) measurements were carried out in 7 different points in each OT, alternating two conditions: a) doors closed; b) opening/closing the main door twice per minute. For each spot, in each condition, we recorded for several minutes the following parameters: particles (0.3, 0.5, 1, 3, 5, 10µ), room temperature (Ta), Relative Humidity (Rh), airspeed (Va). Comparison with the Wilcoxon test were made using STATA 14. Results: In laminar flow, classified with better ISO levels (4), opening and closing the door the PM, for any size, increased not significantly (p > 0.05). The OTs with turbulent flows (ISO 5-6) had a higher particulate level than the laminar ones and greater variations with door openings. OT-A worsened significantly for all particles (p < 0.05) closing/opening the door. In contrast, OT-B and OT-C had a significant reduction of PM (p < 0.05). All 5 OTs had pressure falling to 0 at door opening; Ta, Rh and Va may be affected by different type air flows and design. Conclusions: OTs parameters during door openings are influenced by different ventilation systems and room design. Laminar flows OTs are less affected, but innovative turbulent flows OTs can be just as effective. Key messages: The operating rooms are affected by the door opening. Laminar flows operating rooms are less influenced by door openings than turbulent flows ones. Turbulent flow rooms have different performance depending on their construction characteristics.